Manganese-carbon composite controlled-release material as well as preparation method and application thereof
By developing manganese-carbon composite controlled release materials, optimizing the ratio of organic/inorganic electron donors, regulating the carbon release rate and manganese circulation process, the problem of high process cost and insufficient sustainability in low carbon nitrogen treatment is solved, and the problem of low carbon and nitrogen treatment is achieved. Efficient and stable nitrogen removal and phosphorus removal effects.
Patent Information
- Application Number
- CN202510038034.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
The prior art has problems such as high process operation cost, poor environmental benefits, insufficient sustainability of denitrification and incomplete manganese circulation when treating low-carbon nitrogen ratio wastewater.
Develop a manganese-carbon composite controlled release material, which can improve nitrogen removal efficiency and stability by optimizing the organic/inorganic electron donor ratio, regulating the carbon release rate and manganese cycle process, and achieve synchronous nitrogen removal and phosphorus removal and adaptive continuous nitrogen removal. .
It significantly improves the stability and sustainability of nitrogen removal efficiency and carbon release performance, extends the service life of the material, and achieves deep nitrogen removal treatment of low-polluting water.
Smart Images

Figure CN119461656A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of wastewater treatment, and in particular relates to a low carbon-nitrogen ratio wastewater treatment technology. Background Art
[0002] The water quality of many low-polluting river water, sewage treatment plant tailwater, urban surface runoff, agricultural runoff (including rural decentralized domestic sewage) can meet the "Urban Sewage Treatment Plant Pollutant Discharge Standard", but is still inferior to the Class V surface water quality standard value. These low-polluting waters are large in volume, lack biodegradable organic matter, and have a common problem of low carbon-nitrogen ratio (C / N<5.0).
[0003] Most treatment measures use the method of directly adding liquid carbon source (LCS) for deep denitrification. In the short term, this method is low-investment and easy to implement, but in the long term, its process operation cost is high and the environmental benefits are poor, which is mainly reflected in the continuous addition of carbon source, high residual sludge production and large carbon emissions. It is urgent to find a high-efficiency, low-energy consumption, low carbon-nitrogen ratio wastewater treatment technology.
[0004] Solid phase denitrification technology for low carbon-nitrogen ratio wastewater treatment is mainly developed based on natural solid carbon sources or artificial synthetic carbon sources. The natural solid carbon sources (SCS) that are currently studied are mainly cheap and readily available agricultural waste (AW), such as sawdust, straw, rice husks, cotton, corn cobs, peanut shells, etc. However, this type of natural material generally releases excessive dissolved organic matter (DOM) in the initial stage of the reaction, and even quickly releases a large amount of colored dissolved organic matter (CDOM) to cause apparent pollution. In the later stage of the reaction, the difficult-to-degrade components such as lignin decompose slowly, and the sustainability of denitrification is insufficient. In addition, some plant carbon sources will release nutrients such as N and P during the carbon release process, causing secondary pollution. At the same time, the loose surface of natural materials makes them sensitive to changes in external conditions and easily cause blockage problems.
[0005] Autotrophic denitrification has more environmental and economic advantages than heterotrophic denitrification: low sludge production, relatively low cost, no need to add external carbon source, and reduced secondary organic carbon pollution. The new type of autotrophic denitrification driven by manganese has become a research hotspot in recent years. Using low-valent manganese as an electron donor to achieve manganese oxidation coupling with NO2 - -N or NO3 - The denitrification process of -N is called NDMO. NDMO is coupled with the manganese ammonia oxidation (Mnammox) process to form a nitrogen conversion process driven by manganese cycle (Equation 1-Equation 4). At the same time, the associated biological manganese oxide (BMO) has a larger specific surface area, higher redox potential, stronger adsorption capacity and higher catalytic activity. High-valent manganese oxides can promote the degradation of refractory organic matter and use their products as a denitrification carbon source to make NO3 --N removal rate is further improved. However, the use of only low-valent manganese as an inorganic electron donor to drive autotrophic denitrification is insufficient, and excessive introduction of low-valent manganese will also cause secondary pollution.
[0006] <![CDATA[3MnO2+ NH4 + + 4H + → 3Mn 2+ + NO2 - + 4H2O]]> (1) <h2 style=";text-align:left;direction:ltr"><![CDATA[4MnO2+ NH4 <h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> +6H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> → 4Mn<h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> + NO3<h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> + 5H2O]]><h2 style=";text-align:left;direction:ltr"> (2) <![CDATA[3MnO2+ 2NH4 + + 4H + → 3Mn 2+ + N2+ 6H2O]]> (3) <h2 style=";text-align:left;direction:ltr"><![CDATA[2NO3 <h2 style=";text-align:left;direction:ltr"> - <h2 style=";text-align:left;direction:ltr"> + 5Mn<h2 style=";text-align:left;direction:ltr"> 2+ <h2 style=";text-align:left;direction:ltr"> + 4H2O → N2+ 5MnO<h2 style=";text-align:left;direction:ltr"> x <h2 style=";text-align:left;direction:ltr"> +8H<h2 style=";text-align:left;direction:ltr"> + <h2 style=";text-align:left;direction:ltr"> ]]><h2 style=";text-align:left;direction:ltr"> (4)
[0007] At present, manganese-rich deep denitrification and purification materials have the following problems: ① Manganese oxides are mostly insoluble substances, and the utilization of high-valent manganese by manganese autotrophic denitrifying bacteria is limited, and the reaction kinetics are slow, so that the required residence time in the anaerobic bioreactor is usually more than 7 days, affecting the overall denitrification efficiency. Therefore, how to improve the bioavailability of high-valent manganese and shorten the hydraulic retention time through filler modification is a key technical problem that needs to be solved urgently in the denitrification process based on manganese-rich fillers. ② During use, manganese oxides will cause crusting problems due to surface passivation, resulting in incomplete manganese circulation and reduced efficiency; how to continuously produce biological manganese oxide with a large specific surface area and high activity in the bioreactor is a key technical problem that needs to be solved urgently based on the manganese-rich filler bioreactor to maintain the balance of manganese oxidation and manganese reduction, realize manganese circulation, and drive nitrogen conversion for a long time.
[0008] Carbon materials are excellent mediators of electron transfer, and adding carbon materials can improve the electron transfer efficiency of manganese redox processes. This type of manganese-carbon composite material is mainly prepared by direct chemical synthesis methods such as high temperature and high pressure grafting. For example, patent application CN110416530B discloses a flower-shaped manganese dioxide / carbon composite material and its preparation method and application, and patent number CN104392849B discloses a method for preparing a manganese dioxide / carbon composite material, which belongs to the field of secondary batteries. Similarly, patent number CN115650302B discloses a new type of manganese oxide carbon composite material with a branched structure and its preparation method, in which manganese oxide colloid prepared by chemical reagents is sealed and heated and in situ grafted to the surface of carbon material to form a composite material. In theory, this type of composite material can use carbon components to enhance extracellular electron transfer during denitrification and improve the electron utilization rate of denitrifying microorganisms. However, in the process of preparing such composite materials for improving battery activity, the selected carbon materials are commercial high-conductivity carbon materials such as activated carbon, carbon nanotubes, graphene, acetylene black ACEF, conductive carbon black Super P, Ketjen black EC-300J or Capote black, which have high raw material costs and have almost no ability to serve as a denitrification carbon source.
[0009] Natural plant carbon sources can serve as growth substrates for autotrophic denitrifying bacteria and triggers for nitrogen conversion metabolism, coupling heterotrophic denitrification with autotrophic denitrification to achieve deep denitrification of low carbon-nitrogen ratio wastewater. x- slow-release carbon source combined with enhanced low C / N sewage deep denitrification filler and preparation method thereof, but the slow-release solid carbon is only the modified sodium hydroxide of crushed agricultural waste, and the technical means of enhancing the deep denitrification of low C / N sewage is to add MnO x It is simply combined with a slow-release carbon source. This will cause the following problems: ① Alkaline modification mainly controls the initial carbon release rate by partially eliminating dissolved organic matter, but has limited impact on the stability and sustainability of the carbon release process; ② The electron transfer and mass transfer efficiency between manganese fillers and carbon fillers is insufficient, and manganese reduction, carbon decomposition, heterotrophic and autotrophic denitrification are not unified in time and space, making it difficult to achieve synergistic denitrification; ③ Plant carbon sources produce a large amount of H through microbial hydrolysis and fermentation. + Manganese autotrophic denitrification is also an acid-producing process, which makes the pH in the anaerobic bioreactor unstable and reduces the biochemical activity of denitrifying microorganisms. Therefore, similar studies only focus on the denitrification functions of manganese-rich materials and carbon materials, and the huge potential of using manganese-carbon composite materials to regulate the carbon release process and manganese circulation process has not been tapped, lacking the overall consideration of the manganese-carbon composite denitrification process.
[0010] In recent years, there have also been studies on the use of artificially synthesized carbon sources to melt composite manganese oxides. For example, patent application No. CN116239224B discloses a composite material for artificial wetlands, its preparation method and application, and proposes to compound manganese oxide with degradable solid carbon material polycaprolactone and use it for artificial wetland denitrification. However, in the application process, it was found that polycaprolactone was used in large quantities, was expensive, had a single chemical composition, and took a long time for microbial biofilm to form. Patent application No. CN103157435B discloses a method for preparing a microbial-based manganese-carbon composite material, which is obtained by manganese oxidizing bacteria generating secondary manganese oxide in a carbon-rich culture medium (yeast extract, peptone, agar), and then activating it. However, the microbial culture cycle is long and the yield is low. The material needs to be activated at high temperature before use, which makes it difficult to expand its application. In addition, this type of composite material mainly removes pollutants through physical and chemical effects such as adsorption, and has limited adsorption capacity.
[0011] Therefore, it is necessary to develop manganese-carbon composite controlled-release materials with low raw material cost, simple preparation method and sustainability, and use them for denitrification of low carbon-nitrogen ratio wastewater. Summary of the invention
[0012] In order to solve the problems of the prior art, the present invention provides a manganese-carbon composite controlled-release material and a preparation method and application thereof. The manganese-carbon composite controlled-release material of the present invention optimizes the organic / inorganic electron donor ratio to regulate the release rate, enhances the system denitrification efficiency and stability, realizes synchronous denitrification and phosphorus removal and adaptive continuous denitrification, and has excellent denitrification and phosphorus removal performance.
[0013] The object of the present invention is to provide a manganese-carbon composite controlled-release material, which comprises the following components: a manganese-rich mineral, a natural carbon source, a gelling material, an aggregate, an additive and a foaming agent. The mass ratio of manganese-rich mineral: natural carbon source: cementitious material: aggregate: additive is 40-100: 4-10: 40-100: 40-60: 20-60. The amount of foaming agent used is 0.015%-0.2% of the sum of the mass of manganese-rich minerals, natural carbon sources, cementitious materials, aggregates and additives. The mass of the manganese-rich mineral accounts for 20%-35% of the mass of all components, and the mass of the natural carbon source accounts for 1.5%-5.0% of the mass of all components. The particle size of the natural carbon source is 20-200 meshes, and the particle size of the manganese-rich mineral is 20-200 meshes.
[0014] The manganese-carbon composite controlled-release material of the present invention optimizes the ratio of organic / inorganic electron donors, realizes the regulation of carbon release rate and manganese circulation process by means of the interaction between manganese and carbon, and enhances the denitrification efficiency and stability of the system; significantly improves the efficiency of electron transfer and mass transfer, realizes the synergistic denitrification of manganese reduction, carbon decomposition, heterotrophic and autotrophic denitrification, improves the denitrification efficiency, makes the carbon release performance more stable, and achieves better denitrification effect; the carbon release process has better stability and sustainability, improves the utilization rate of manganese oxides, and is easy for microbial biofilm to form, thereby shortening the hydraulic retention time.
[0015] Furthermore, the above natural carbon source is obtained by alkali pretreatment. The pretreatment conditions are: pretreatment with a sodium hydroxide solution with a concentration of 0.2-0.5M, a solid-liquid ratio of the natural carbon source to the sodium hydroxide solution of 1:5-10, a soaking time of 16-48h, a soaking temperature of 20-40°C, a water washing number of ≥3, a drying temperature of 40-60°C, and a drying time of 12-48h. After the natural carbon source is treated with alkali, the crystal structure between lignin and hemicellulose can be broken, thereby improving bioavailability.
[0016] Preferably, the natural carbon source includes at least one of plant waste and wetland plant residues. The plant waste includes at least one of wheat straw, rice straw, reed and corn cob. The wetland plant includes at least one of reed, water plantain and Spartina alterniflora.
[0017] Preferably, the manganese-rich mineral includes at least one of natural manganese sand, pyrolusite, psilomelane and rhodochrosite.
[0018] In the present invention, the cementitious material includes at least one of cement, silicate material, and synthetic resin. The alkalinity generated by cement and other cementitious materials neutralizes the acidity generated by the hydrolysis of natural carbon sources and the autotrophic denitrification process, and has high pH stability. The aggregate includes at least one of coarse sand, gravel sand, angular gravel, crushed stone, and limestone.
[0019] The additive includes at least one of steel slag, fly ash, attapulgite, gypsum, bentonite and diatomaceous earth. Steel slag can be used to improve the strength and durability of the composite material, and can also make the composite material have a certain conductivity. At the same time, steel slag contains Ca 2+ Mg 2+ 、Al 3+ Ion Energy and PO4 3- Form a precipitate and enhance the phosphorus removal performance of the composite material.
[0020] In addition, cement, gypsum, fly ash and other components contain a large amount of calcium and magnesium ions, which can effectively adsorb, precipitate and remove phosphorus, while also neutralizing the acidity generated by processes such as hydrolysis and fermentation, and enhancing the pH stability of the system.
[0021] Preferably, the foaming agent includes at least one of a carbonate inorganic foaming agent, a rosin soap foaming agent, an animal or plant protein foaming agent, and pulp waste liquid.
[0022] The present invention also aims to provide a method for preparing the above-mentioned manganese-carbon composite controlled-release material, comprising the following steps: (1) uniformly mixing the above-mentioned manganese-rich mineral, natural carbon source, cementitious material, aggregate and additive according to the above-mentioned proportion to obtain a mixed material; (2) Spraying a foaming agent dilution solution having a foaming agent content of 0.05wt%-0.5wt% on the surface of crushed stone particles with a particle size of 2-6 mm, adding the solution to a drum granulator, starting the drum granulator, pouring the mixed material obtained in step (1) into the drum granulator, spraying a certain amount of water intermittently during the rolling process, obtaining manganese-carbon composite particles with a particle size of 3-10 mm, taking the manganese-carbon composite particles out of the drum granulator, and naturally curing them for 3-7 days to obtain an agglomerated coated manganese-carbon composite controlled-release material.
[0023] Preferably, the mass ratio of the above-mentioned manganese-rich mineral, natural carbon source, cementitious material, aggregate and additive is 40-100:5-10:50-80:40-60:26-50.
[0024] The present invention also aims to provide another method for preparing a manganese-carbon composite controlled-release material, comprising the following steps: (1) uniformly mixing the above-mentioned manganese-rich mineral, natural carbon source, cementitious material, aggregate and additive according to a proportion to obtain a mixed material; (2) Adding a foaming agent diluent having a foaming agent content of 0.05wt%-0.5wt% to the mixed material obtained in step (1), stirring until viscous, air-drying for 1-3 days, and curing at a temperature of 15-25°C for 7-15 days, spraying a certain amount of water every 1-2 days during curing, and finally obtaining a coagulated and solidified manganese-carbon composite controlled-release material after mechanical crushing.
[0025] Preferably, the mass ratio of the above-mentioned manganese-rich mineral, natural carbon source, cementitious material, aggregate and additive is 60-80:4-10:40-60:40-60:30-60.
[0026] The foaming agent in the present invention needs to be diluted to a foaming agent dilution liquid with a mass fraction of 0.05%-0.5% before use. By changing the mass fraction of the foaming agent during the preparation process, the pores, specific surface area and density of the material can be regulated, thereby achieving the regulation of the carbon release rate.
[0027] The specific surface area of the manganese-carbon composite controlled-release material of the present invention is 300-400m 2 / kg.
[0028] The present invention also aims to apply the above manganese-carbon composite controlled-release material to the filler of artificial wetlands, biofilters, and flooded areas of bioretention systems.
[0029] The present invention also aims at applying the above-mentioned manganese-carbon composite controlled-release material to the treatment of tailwater from sewage treatment plants, rural domestic sewage, farmland non-point source treatment, and initial rainwater purification.
[0030] The manganese-carbon composite controlled-release material of the present invention selects appropriate raw material ratios and filling methods according to the water quality and quantity characteristics of sewage treatment plant tail water, farmland drainage, and initial rainwater, and is targeted and flexible. It is used as a filler in a tail water treatment biofilter with excellent nitrogen and phosphorus removal performance. Compared with an inert filler biofilter, the removal rate is increased by more than 70% when the residence time is 1 day.
[0031] The present invention also provides a method for preparing a manganese-carbon controlled-release material composite porous plate, which uses P20 or P20+Ni steel as a mold, with a mold length of 160-200 cm, a length-to-width ratio of 5:3-16:9, a mold bottom thickness of 3-5 cm, an edge thickness of 25-30 cm, and an edge width of 5-10 cm. Cylinders with a diameter of 15-25 cm and a height of 8-12 are evenly arranged in the mold at a spacing of 8-10 cm. Water is added to the above-mentioned manganese-carbon controlled-release material at a solid-liquid mass ratio of 1.5-2:1, and the mixture is injected into the mold after being stirred evenly. The slurry has a depth of 15-20 cm, and is air-dried and molded before demolding to form a manganese-carbon controlled-release material composite porous plate.
[0032] The present invention also provides an application of the above-mentioned manganese-carbon controlled-release material composite porous plate. Anchor piles are pre-constructed in an artificial wetland. The distance between the piles is 100-115 cm. Openings are provided around the anchor piles. The opening depth is 20-23 cm. The manganese-carbon controlled-release material composite porous plate is inserted into the anchor pile openings in a mortise and tenon manner to form a functional artificial wetland based on manganese-carbon controlled-release material.
[0033] Compared with the prior art, the present invention has the following beneficial effects: (1) The manganese component in the manganese-carbon composite controlled-release material of the present invention enhances the stability and sustainability of carbon release. The manganese oxide in the manganese-rich mineral has strong oxidizing properties and can oxidize the difficult-to-degrade organic matter in the plant carbon source into small molecular organic matter that is easily utilized by denitrifying microorganisms, thereby improving the effectiveness of the plant carbon source and promoting the degradation and utilization of the residual carbon source in low-pollution water. Manganese ions dissolve from the composite material, promoting the erosion of the carbon skeleton, which is beneficial to the rapid biofilm formation of the composite material in the early stage of the reaction and promoting the release of the carbon source inside the composite material in the later stage of the reaction. The intermediate products of the decomposition of the plant carbon source (such as proteins) combine with manganese to form a manganese oxide-organic complex, which can buffer the organic carbon release process and improve the stability and sustainability of the carbon source release. (2) The manganese-carbon coupling of the present invention effectively prevents the failure of manganese-rich functional materials caused by surface passivation. The formation of manganese oxide-organic complex can change the dense morphology of the surface oxide, alleviate the surface passivation and crusting problems of high-valent manganese at the interface during the reaction of manganese-rich minerals, and improve their solubility and reaction activity; (3) Lignin in plant waste is rich in semiquinone structures that can act as electron shuttles. Multivalent manganese in manganese-rich minerals can also mediate electron transfer through redox cycles. Both can improve the utilization of organic carbon sources by microorganisms and the efficiency of denitrification. Manganese-rich minerals themselves can drive biological denitrification processes such as manganese ammonia oxidation and nitrate-dependent manganese oxidation. They can also remove ammonia nitrogen through processes such as adsorption and chemical oxidation. They have diverse denitrification pathways, sufficient denitrification power, and short startup time. (4) The manganese-carbon composite material achieves simultaneous nitrogen and phosphorus removal and adaptive continuous nitrogen removal. In the early stage of use, the cementitious material wrapped around the manganese-carbon delays the release of the internal organic carbon source through physical action, avoiding excessive carbon release and secondary pollution caused by the process of dissimilatory nitrate reduction to ammonium (DNRA), thereby improving the controllability of the heterotrophic denitrification process. During use, the manganese-carbon interaction buffers the release rate of organic electron donors and enhances the dissolution of inorganic electron donors. In response to different carbon-nitrogen ratio environments, microorganisms adaptively utilize organic / inorganic electron donors to achieve multi-electron donor synergistic denitrification. In the later stage of use, the difficult-to-degrade components of natural carbon sources can be used as carbon sources or electron shuttles. Under the condition of sufficient wastewater carbon source, the composite material acts as an electron shuttle to mediate the decomposition of organic carbon sources and heterotrophic denitrification. Under low carbon-nitrogen ratio conditions, microorganisms use the chelated manganese-carbon components derived from the composite material as energy and electron donors to synergistically denitrify with the biological manganese oxides generated by the previous biochemical reaction, thereby improving the denitrification efficiency. (5) Cement, gypsum, fly ash and other components in cementitious materials and additives contain a large amount of calcium and magnesium ions, which can effectively adsorb and precipitate phosphorus removal. The alkalinity generated by cement and other cementitious materials neutralizes the acidity generated by the hydrolysis of plant carbon sources and autotrophic denitrification, and has high pH stability. (6) The manganese-carbon composite controlled-release material of the present invention has the characteristics of large specific surface area, controllable density, and easy microbial biofilm formation. It can continuously produce biological manganese oxides with high activity, maintain the balance of manganese oxidation and manganese reduction, realize manganese circulation, and drive nitrogen conversion in a long term, which significantly improves the overall efficiency of the denitrification process, improves the denitrification performance of low-pollution water, and prolongs the service life of the material.
[0034] In summary, the manganese-carbon composite controlled-release material of the present invention optimizes the carbon release process and the manganese circulation process, and realizes the regulation of the carbon release rate and the manganese circulation process by means of the interaction between manganese and carbon. The overall denitrification efficiency is significantly improved, and simultaneous denitrification and phosphorus removal and adaptive continuous denitrification are achieved. The raw materials required for the preparation of the manganese-carbon composite controlled-release material are environmentally friendly and inexpensive, the preparation process is simple, the preparation cost is low, and the resource utilization of waste fiber materials is realized. It can be widely used in application scenarios such as deep treatment of tail water from sewage treatment plants, rural agricultural sewage treatment, and initial rainwater purification. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a product picture of manganese-carbon composite controlled-release material; Figure 2 This is the result of the denitrification test in a micro anaerobic bottle; Figure 3 The denitrification performance of the biofilter reaction column; Figure 4 Schematic diagram of nitrogen conversion process in artificial wetlands based on manganese-carbon composite materials; Figure 5 Schematic diagram of the mold structure for preparing the manganese-carbon controlled-release material composite porous plate; Figure 6 This is the installation method of manganese-carbon controlled-release material composite porous plate in artificial wetland. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The embodiment of the present invention uses modified plant waste as a natural carbon source, crushed natural manganese-rich ore as an inorganic electron donor, cement, limestone, etc. as an inorganic binder and pH regulator, and plant fiber and protein slurry as a pore-forming agent.
[0038] Plant waste includes wheat straw, rice straw, reed, corn cob, etc., which are crushed and used as carbon-rich matrix. The pretreatment process of plant waste includes: putting the plant waste in a crusher to crush and screen, then soaking it in sodium hydroxide solution, repeatedly washing it with water and drying it, and sealing it at room temperature. The purpose is to break the crystal structure between lignin and hemicellulose and improve bioavailability.
[0039] The conditions for pretreatment of plant waste are as follows: particle size of 20-200 mesh, concentration of sodium hydroxide solution of 0.2-0.5M, solid-liquid ratio of 1:5-10, soaking time of 16-48h, soaking temperature of 20-40℃, water washing times ≥3, drying temperature of 40-60℃, and drying time of 12-48h.
[0040] Manganese-rich minerals include manganese sand, manganese carbonate ore, birnessite, etc., which are crushed to serve as manganese-rich matrix. The pretreatment process and conditions of manganese-rich minerals are as follows: the purchased manganese-rich mineral materials are added to a crusher and crushed to a particle size of 20 to 200 meshes.
[0041] Aggregates include inert particles such as coarse sand, gravel sand, angular gravel, crushed stone, limestone, etc.
[0042] Cementitious materials include inorganic binders such as cement and fly ash, which are used for bonding granulation.
[0043] Foaming agents include carbonate inorganic foaming agents or rosin soap foaming agents, animal and plant protein foaming agents, pulp waste liquid and other organic foaming agents, which are used for foaming and pore formation.
[0044] The pretreated plant waste, manganese-rich material and the above components are mixed in a certain proportion and granulated by a drum wrapping method or agglomeration-crushing method.
[0045] The drum granulation method is used to prepare the agglomerated coated manganese-carbon composite controlled release material. Specifically, manganese-rich materials, plant carbon source powder, cement, aggregates such as gravel and sand, additives (fly ash, steel slag, attapulgite, gypsum, etc.) are mixed in a mass ratio of 40-100: 5-10: 50-80: 40-60: 26-50, stirred evenly, and a mixed material is obtained; a foaming agent diluent with a foaming agent content of 0.05%-0.5% is sprayed on the surface of crushed stone particles with a particle size of 2-6 mm, and a drum granulator is added; the granulator containing crushed stone is started, and the mixed material is slowly poured into it, and a certain amount of water is sprayed intermittently during the rolling process to obtain manganese-carbon composite particles with a particle size of 3-10 mm; the manganese-carbon composite particles are taken out from the drum granulator, and naturally cured for 3-7 days to obtain an agglomerated coated manganese-carbon composite material.
[0046] The cement agglomeration method is used to prepare a coagulation-cured manganese-carbon composite controlled-release material. Specifically, manganese-rich materials, plant carbon source powders, ordinary silicate cement, aggregates such as gravel and sand, and additives (non-metallic mineral material powders such as fly ash, steel slag, gypsum, bentonite and diatomaceous earth) are mixed in a mass ratio of 60-80:4-10:40-60:40-60:30-60, stirred evenly, and a mixed solid material is obtained; an aqueous solution with a foaming agent content of 0.05%-0.5% and accounting for 30%-40% of the total mass of the mixed solid material is added, stirred until viscous, and air-dried for 1-3 days; cured at a temperature of 15-25°C for 7-15 days, spraying a certain amount of water every 1-2 days during curing, and finally obtained a coagulation-cured manganese-carbon composite controlled-release material after mechanical crushing.
[0047] Example 1 Preparation of agglomerated coated manganese-carbon composite controlled-release material S1. Mix the crushed natural manganese sand powder, corn cob powder, ordinary Portland cement, coarse sand or gravel sand, steel slag, fly ash and gypsum in a mass ratio of 40:8:80:40:10:10:10, stir evenly and obtain a mixed material; S2, spraying the surface of crushed stone particles with a particle size of 3 to 5 mm with a diluted solution of a vegetable protein foaming agent with a content of 0.5 wt%, and adding the particles to a drum granulator; S3, start the granulator containing crushed stone, roll it at a speed of 20 rpm / min, use an electric sprayer to spray 1 mL of water every 3 seconds, and slowly pour the mixed material into it after each water spray to obtain manganese-carbon composite particles with a particle size of 3 to 7 mm; S4, after taking out the manganese-carbon composite particles from the drum granulator, naturally curing for 7 days to obtain the agglomerated coated manganese-carbon composite controlled-release material MC1, such as Figure 1 shown.
[0048] Example 2 Preparation of agglomerated coated manganese-carbon composite controlled release material S1. Mix the crushed natural manganese sand powder, corn cob powder, ordinary Portland cement, coarse sand or gravel sand, steel slag, fly ash, and gypsum in a mass ratio of 60:8:60:40:10:10:10, stir evenly, and obtain a mixed material; S2, spraying the surface of crushed stone particles with a particle size of 3 to 5 mm with a diluted solution of a vegetable protein foaming agent with a content of 0.5 wt%, and adding the particles to a drum granulator; S3, start the granulator containing crushed stone, roll it at a speed of 20 rpm / min, use an electric sprayer to spray 1 mL of water every 3 seconds, and slowly pour the mixed material into it after each water spray to obtain manganese-carbon composite particles with a particle size of 3 to 7 mm; S4, after taking out the manganese-carbon composite particles from the drum granulator, naturally curing for 7 days to obtain the agglomerated coated manganese-carbon composite material MC2, such as Figure 1 shown.
[0049] Example 3 Preparation of coagulation-solidified manganese-carbon composite controlled-release material S1. Mix the crushed natural manganese sand powder, corn cob powder, ordinary Portland cement, coarse sand or gravel sand, steel slag, bentonite, and gypsum in a mass ratio of 80:8:60:60:10:35:5, stir evenly, and obtain a mixed solid material; S2, adding an aqueous solution of a vegetable protein foaming agent with a content of 0.5wt% and accounting for 35% of the total mass of the mixed solid material, stirring until viscous, and air-drying for 3 days; S3. Curing at a temperature of 15-25°C for 7 days, spraying a certain amount of water every 1-2 days during curing; S4. Finally, after mechanical crushing, a coagulated and solidified manganese-carbon composite material MC3 is obtained, such as Figure 1 MC3 shown.
[0050] Example 4 Preparation of coagulation-solidified manganese-carbon composite controlled-release material S1. The crushed natural manganese sand powder, corn cob powder, ordinary Portland cement, coarse sand or gravel sand, steel slag, bentonite or diatomaceous earth, and gypsum are mixed in a mass ratio of 80:4:60:60:10:35:5, and stirred evenly to obtain a mixed solid material; S2, adding an aqueous solution with a plant protein foaming agent content of 0.5wt% and accounting for 40% of the total mass of the mixed solid material, stirring until viscous, and air-drying for 3 days; S3. Curing at a temperature of 15-25°C for 7 days, spraying a certain amount of water every 1-2 days during curing; S4, after mechanical crushing, a coagulated and solidified manganese-carbon composite material MC4 is obtained, such as Figure 1 MC4 shown.
[0051] Application Example 1 Four 250 mL micro anaerobic bottles were filled with 100 g of the manganese-carbon composite controlled-release materials MC1, MC2, MC3, and MC4 prepared in the above examples, and 200 mL of synthetic wastewater was added. - -N concentration is about 30mg / L, sludge concentration MLVSS is about 200mg / L. Let it stand for 3 days to allow microorganisms to form biofilms, and then drain the remaining solution. Re-configure new sludge without activated sludge, NO3 - -N concentration is about 30mg / L synthetic wastewater and added into the above four 250mL micro anaerobic bottles. Hydraulic retention time is 3 days. Sampling test of effluent NO3 - -N concentration. The denitrification test results of manganese-carbon composite controlled-release materials MC1, MC2, MC3, and MC4 in micro anaerobic bottles are shown in Figure 2. Figure 2As shown. Figure 2 It can be seen that the nitrate nitrogen removal rates of manganese-carbon composite controlled-release materials MC1, MC2, MC3, and MC4 are all greater than 75%.
[0052] Application Example 2 Manganese-carbon composite controlled-release materials MC3 and MC4 were filled in a reaction column with a diameter of 10 cm and a height of 50 cm, inoculated with activated sludge with MLVSS of about 300 mg / L, and left to stand for three days to allow microorganisms to form biofilms. Another group of blank control groups CK was set up, filled with gravel inert fillers of the same particle size.
[0053] Configuration containing NO3 - -N concentration is about 30mg / L, PO4 3- -P concentration of about 3.0mg / L synthetic wastewater, while adding other macro and trace elements, including MgCl2·6H2O 61.0mg / L, CaCl2 33.2mg / L, CuSO4·5H2O 0.03mg / L, ZnSO4·7H2O 10.8mg / L, NaMoO4·2H2O 0.25mg / L, CoCl2·6H2O 0.025mg / L and H3BO 36.2mg / L. These macro and trace elements are the main elements of cell components and enzymes, which are essential for the formation of cell structure and the maintenance of enzyme activity. These macro and trace elements are to ensure the normal growth and metabolism of microorganisms, build and maintain stable biofilms, and improve the efficiency and stability of biochemical reactions.
[0054] The acclimatization and cultivation lasted for 3 cycles, and the hydraulic retention time (HRT) was 3 days. After the acclimatization and cultivation, the operation phase began, and the hydraulic retention time was 2 days. The operation lasted for 3 cycles, and the effluent NO3 was sampled and tested at different time points in each cycle. - -N concentration. Average NO3 in effluent - -N concentration as Figure 3 shown.
[0055] When the hydraulic retention time was 24h, the nitrate removal rates of MC3 and MC4 were 90.0% and 72.8%, respectively; when the hydraulic retention time was 40h, the removal rates of MC3 and MC4 for nitrate nitrogen were both above 94%, while the removal rate of the control group was almost zero. This shows that without adding any liquid carbon source, relying on the manganese-carbon composite material can significantly promote the denitrification process and efficiently remove NO3 - -N.
[0056] Application Example 3: Nitrogen conversion process in artificial wetlands based on manganese-carbon composite controlled-release materials The nitrogen conversion process of artificial wetland based on the manganese-carbon composite controlled-release material of the present invention is as follows Figure 4As shown. The manganese-carbon composite controlled-release material contains the main active ingredients manganese oxide and plant carbon source. In the aerobic zone of the artificial wetland, ammonia nitrogen can be converted into carbon by MnO x Oxidation, or converted into nitrate nitrogen under the action of nitrifying bacteria. In the anaerobic and anoxic zone of artificial wetlands, plant carbon sources release a certain amount of dissolved organic matter (DOM), which is degraded into small molecular organic carbon sources under the action of manganese oxides and microorganisms, promoting heterotrophic denitrification; low-valent manganese generated by the reduction of manganese oxides acts as an electron donor for denitrifying bacteria, driving manganese autotrophic denitrification; in the biochemical process, low-valent manganese is reoxidized to form biological manganese oxides (BMO), which can serve as an electron acceptor for ammonia oxidation, promoting the removal of ammonia nitrogen through chemical catalytic oxidation or manganese ammonia oxidation (Mnammox), and on the other hand, it can combine with organic acids, intermediates in the decomposition of plant carbon sources, to form MnO x -Organic complexes, as electron storage carriers, prolong the release time of electron donors and ensure sustainable denitrification.
[0057] During the use of the manganese-carbon composite controlled-release material of the present invention, the proportion of organic / inorganic electron donors can be adjusted by adjusting the mass fraction of manganese and carbon in the composite material, thereby regulating the filler's denitrification performance in dealing with wastewater under different nitrogen loads and carbon-nitrogen ratios.
[0058] Application Example 4 The coagulation-solidified manganese-carbon composite controlled-release material prepared in accordance with Example 3 or 4 is prepared into a manganese-carbon controlled-release material composite porous plate for application in artificial wetlands.
[0059] P20 or P20+Ni steel is used as the mold, with a mold length of 160-200cm, a length-to-width ratio of 5:3-16:9, a mold bottom thickness of 3-5cm, an edge thickness of 25-30cm, and an edge width of 5~10cm. Cylinders with a diameter of 15-25cm and a height of 8-12 are evenly arranged in the mold at a spacing of 8-10cm. When in use, the coagulation-curing manganese-carbon composite controlled-release material components prepared in Example 3 or 4 are added in a proportion, and water is added at a solid-liquid mass ratio of 1.5-2:1. After stirring evenly, the slurry is injected into the mold with a depth of 15-20cm. After air-drying and molding, it is demolded to form a manganese-carbon controlled-release material composite porous plate. The mold structure for preparing the manganese-carbon controlled-release material composite porous plate is as follows Figure 5 shown.
[0060] Anchor piles are pre-built in the artificial wetland, with a distance of 100-115cm between the piles. The anchor piles are opened all around with a depth of 20cm. When in use, the prefabricated manganese-carbon controlled-release composite porous plate is inserted into the anchor pile opening in a "mortise and tenon" manner to form a functional artificial wetland based on manganese-carbon controlled-release material. The installation method of the manganese-carbon controlled-release composite porous plate in the artificial wetland is as follows: Figure 6As shown. Nitrogen and phosphorus pollutants in the water body are efficiently removed by contact with the manganese-carbon controlled-release material composite porous plate. The artificial wetland can achieve efficient nitrogen and phosphorus removal. The manganese-carbon controlled-release material composite porous plate can be assembled or replaced as needed, and has the characteristics of low cost, simple installation and convenient maintenance.
[0061] In summary, the raw materials required for preparing the manganese-carbon composite controlled-release material of the present invention are environmentally friendly and inexpensive, the preparation process is simple, the preparation cost is low, and the resource utilization of waste fiber materials is realized. The manganese-carbon composite controlled-release material of the present invention optimizes the ratio of organic / inorganic electron donors to regulate the release rate, enhances the denitrification efficiency and stability of the system, significantly improves the electron transfer and mass transfer efficiency, realizes synergistic denitrification, has excellent denitrification and phosphorus removal performance, more stable carbon release performance, and has better stability and sustainability for the carbon release process.
[0062] The above embodiments are only used to illustrate the present invention, rather than to limit the present invention. Those skilled in the relevant technical field may make various changes or modifications without departing from the spirit and scope of the present invention. Therefore, all equivalent technical solutions should also belong to the scope of the present invention and should be defined by the claims.
Claims
1. A manganese-carbon composite controlled-release material, characterized in that: The invention comprises the following components: manganese-rich minerals, natural carbon sources, cementitious materials, aggregates, additives and foaming agents; The mass ratio of the manganese-rich mineral, the natural carbon source, the cementitious material, the aggregate, and the additive is 40-100: 4-10: 40-100: 40-60: 20-60; The amount of the foaming agent is 0.015%-0.2% of the sum of the mass of the manganese-rich ore, natural carbon source, aggregate, cementitious material and additives; The mass of the manganese-rich mineral accounts for 20%-35% of the mass of all components, and the mass of the natural carbon source accounts for 1.5%-5.0% of the mass of all components; Wherein, the particle size of the natural carbon source is 20-200 mesh, and the particle size of the manganese-rich mineral is 20-200 mesh; The natural carbon source is obtained by alkali pretreatment, and the pretreatment conditions are: pretreatment with a sodium hydroxide solution with a concentration of 0.2-0.5M, a solid-liquid ratio of the natural carbon source to the sodium hydroxide solution of 1:5-10, a soaking time of 16-48h, a soaking temperature of 20-40°C, a water washing number of ≥3, a drying temperature of 40-60°C, and a drying time of 12-48h; The natural carbon source includes at least one of agricultural waste and wetland plant residues; The manganese-rich mineral includes at least one of natural manganese sand, pyrolusite, psilomelane and rhodochrosite; The cementitious material includes at least one of cement and synthetic resin, the aggregate includes at least one of coarse sand, gravel sand, angular gravel, crushed stone and limestone, and the additive includes at least one of steel slag, fly ash, attapulgite, gypsum, bentonite and diatomaceous earth.
2. The manganese-carbon composite controlled-release material according to claim 1, characterized in that: The specific surface area of the manganese-carbon composite controlled-release material is 300-400 m 2 / kg.
3. A method for preparing the manganese-carbon composite controlled-release material according to claim 1, characterized in that: The following steps are included: (1) uniformly mixing the manganese-rich mineral, natural carbon source, cementitious material, aggregate, and additive according to a proportion to obtain a mixed material; (2) Spraying a foaming agent dilution solution containing 0.05wt% to 0.5wt% of foaming agent on the surface of crushed stone particles with a particle size of 2 to 6 mm, adding the mixture to a drum granulator, starting the drum granulator, pouring the mixture obtained in step (1) into the drum granulator, spraying water intermittently during the rolling process, obtaining manganese-carbon composite particles with a particle size of 3 to 10 mm, and naturally curing for 3 to 7 days to obtain an agglomerated coated manganese-carbon composite controlled-release material.
4. The method for preparing the manganese-carbon composite controlled-release material according to claim 3, characterized in that: The mass ratio of the manganese-rich mineral, the natural carbon source, the cementitious material, the aggregate and the additive is 40-100: 5-10: 50-80: 40-60: 20-50.
5. A method for preparing the manganese-carbon composite controlled-release material as claimed in claim 1, characterized in that: The following steps are included: (1) uniformly mixing the manganese-rich mineral, natural carbon source, cementitious material, aggregate, and additive according to a proportion to obtain a mixed material; (2) Adding a foaming agent diluent having a foaming agent content of 0.05wt%-0.5wt% to the mixed material obtained in step (1), stirring until viscous, air-drying for 1-3 days, and curing at a temperature of 15-25°C for 7-15 days, spraying water every 1-2 days during curing, and finally obtaining a coagulated and solidified manganese-carbon composite controlled-release material after mechanical crushing.
6. The method for preparing the manganese-carbon composite controlled-release material according to claim 5, characterized in that: The mass ratio of the manganese-rich mineral, the natural carbon source, the cementitious material, the aggregate and the additive is 60-80:4-10:40-60:40-60:30-60.
7. Application of the manganese-carbon composite controlled-release material according to claim 1 or 2 or the manganese-carbon composite controlled-release material prepared by the preparation method according to any one of claims 3 to 6, wherein the manganese-carbon composite controlled-release material is used as filler in artificial wetlands, biofilters, and bioretention system flooded areas, and in the purification of sewage treatment plant tailwater, rural domestic sewage, farmland non-point source control, and initial rainwater.
8. A method for preparing a manganese-carbon controlled-release material composite porous plate, characterized in that: P20 or P20+Ni steel is used as the mold, the mold length is 160-200cm, the length-to-width ratio is 5:3-16:9, the mold bottom thickness is 3-5cm, the edge thickness is 25-30cm, the edge width is 5-10cm, and the mold is evenly arranged with 15-25cm diameter and 8-12 height cylinders at intervals of 8-10cm. The components of the manganese-carbon controlled-release material prepared by the preparation method as described in claim 6 are added in a proportion, water is added at a solid-liquid mass ratio of 1.5-2:1, and after stirring evenly, it is injected into a mold with a slurry depth of 15-20 cm. After air-drying and molding, demolding is performed to form a manganese-carbon controlled-release material composite porous plate.
9. An application of the manganese-carbon controlled-release composite porous plate as claimed in claim 8, characterized in that: Anchor piles are pre-constructed in the artificial wetland, with a distance of 100-115 cm between the piles. Openings are arranged around the anchor piles with a depth of 20-23 cm. The manganese-carbon controlled-release material composite porous plate is inserted into the anchor pile openings in a mortise and tenon manner to form a functional artificial wetland based on manganese-carbon controlled-release material.
Citation Information
Patent Citations
Preparation method and application of microbial manganese-carbon composite material
CN103157435B
A kind of preparation method of manganese dioxide / carbon composite material
CN104392849B
A flower-shaped manganese dioxide / carbon composite material, its preparation method and application
CN110416530B
An artificial wetland composite material, its preparation method and application
CN116239224B
Porous slow-release carbon filler and preparation method and application thereof
CN109607763A
Cited By
Birnessite-oxygen releasing agent composite bottom mud repairing material as well as preparation and application methods of birnessite-oxygen releasing agent composite bottom mud repairing material
CN120157313A
Porous complex microbial inoculant for promoting nitrate reduction to produce ammonium as well as preparation method and application of porous complex microbial inoculant
CN120290544A
Steaming-free preparation method and application of manganese autotrophic denitrification biological filter material
CN121134977A